Encapsulated thyroid tumors of follicular cell origin with high grade features (high mitotic rate/tumor necrosis): a clinicopathologic and molecular study() - Rivera, Michael (Hum Pathol, 2009)
Encapsulated thyroid tumors of follicular cell origin with high-grade features (EFHG) are unusual neoplasms. In current classification schemes, they are called atypical adenomas or follicular, papillary, or poorly differentiated carcinoma. When noninvasive, EFHG create a major therapeutic/diagnostic dilemma stemming from their rarity, low-stage, high-grade appearance, and lack of long-term follow-up studies. All cases of EFHG were defined as encapsulated tumors of follicular cell origin with at least 5 mitoses per 10 high-power fields and/or tumor necrosis. Available tissues were subjected to a thyroid carcinoma platform for mass spectrometry high-throughput genotyping, which consisted of 111 known mutations in 16 different genes: BRAF, RET, NRAS, HRAS, KRAS, PIK3CA, AKT1, and other related genes. Twenty-five cases met the selection criteria. Tumor necrosis was present in 56.0% (n = 14). Extensive vascular invasion was identified in 24.0% (n = 6). Eight (32%) of 25 tumors were noninvasive. Twenty-two patients (88%) were free of disease (median follow up: 8.5 years). All 8 noninvasive tumor did not recur despite focal/extensive tumor necrosis in 3 cases and a median follow-up of 11.9 years. EFHG with no vascular invasion did not recur. In patients without distant metastases at presentation (n = 24), 33% (2/6) of patients with extensive angioinvasion relapsed, whereas none of 18 with absent/focal vascular invasion recurred (P = .054). Mutations were found in 10 (45%) of 22 cases tested: 8 had NRAS codon 61, 1 KRAS codon 61, and 1 had coexistent BRAF V600E and AKT1. There was a higher frequency of RAS (9/22, 41%) than BRAF mutations (1/22, 4.5%) (P = .009). Noninvasive EFHG have an indolent behavior even in the presence of extensive tumor necrosis. EFHG with absent vascular invasion have an excellent prognosis despite the frequent occurrence of tumor necrosis. NRAS mutations are the most frequent oncogenic event in EFHG.